Accumulation by dispossession and hegemony in place: The Greek experience. (December 2021) - Milonakis, Dimitris; Drakaki, Elina; Manioudis, Manolis; Tzotzes, Sergios
Seeking to make sense of the Greek crisis Odyssey and the attendant restructuring of the economy, this article focuses on the spatial dynamics of the crisis. To this end, it builds on Harvey's concept of accumulation by dispossession and Gramscian hegemony to evaluate the crisis remedy administered to Greece. An attempt is made to demonstrate dispossession of land, public resources and natural assets as a hegemonic project, as it takes place, linked to specific 'spatio-temporal fixes' of capital during and after the crisis, to be either welcomed or opposed by different stakeholders in civil society and local communities. Assessing the new institutional setting that was enforced upon Greece by its creditors, the Greek case of land dispossession and grabbing is discussed, focusing on representative 'optimum' investment instances to question the rationale and the effectiveness of the emerging post-crisis neoliberal model of economic development.